2009
DOI: 10.1097/yic.0b013e32832ac828
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate therapeutic approach to binge-eating disorder: combined nutritional, psychological and pharmacological treatment

Abstract: Treatment for binge-eating disorder (BED) is directed towards either the physical or psychopathological impairments, and often does not cover all the alterations characterizing the disease. In 30 BED patients, we monitored the effects of three types of 6-month treatment, randomly assigned to one of the three treatment groups, each consisting of 10 patients. Group 1 received a 1700-kcal diet (21% proteins, 27% lipids, 52% carbohydrate), cognitive-behavioural therapy (CBT), sertraline (50-150 mg/day) and topiram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 45 publications
1
36
0
1
Order By: Relevance
“…Эти стили могут сочетаться с психопа-тологической симптоматикой, но такое сочетание далеко не обязательно [16,17]. В рамках каждого из стилей поведения нарушения контроля проис-ходят по разным психофизиологическим механиз-мам.…”
Section: обсуждение и заключениеunclassified
“…Эти стили могут сочетаться с психопа-тологической симптоматикой, но такое сочетание далеко не обязательно [16,17]. В рамках каждого из стилей поведения нарушения контроля проис-ходят по разным психофизиологическим механиз-мам.…”
Section: обсуждение и заключениеunclassified
“…Fruits and vegetables were included three to four times a day. Meals were recommended to be consumed five or six moments a day to prevent excessive hunger, and a food replacement list was offered [12,23].…”
Section: Methodsmentioning
confidence: 99%
“…On this purpose, the education to healthier eating and life styles, and the modification of dysfunctional thoughts and habits are essentials. The most evaluated and developed intervention for BED includes behavioral (BT) and Cognitive-Behavioral Therapies (CBT) [11,12]. Behavioral treatments, focused on diet and lifestyle modification, and caloric restrictions should be moderate, and a normal or hypo caloric diet seems to be the best strategy to prevent bingeing.…”
Section: Introductionmentioning
confidence: 99%
“…19,21,22 Between 30% and 50% of people with BED are also obese 17,23 and obesity research has demonstrated that when CBT is compared with behavioural weight loss interventions (calorie restriction and exercise) for BED, CBT results in greater treatment effects than other interventions after both short-and long-term follow-up. 18,19,24 Patient selection and the way in which CBT is provided may play a role in terms of treatment efficacy for both BED and non-BED obese populations.…”
Section: Cognitive-behavioural Therapymentioning
confidence: 99%